2019
DOI: 10.1111/cga.12361
|View full text |Cite
|
Sign up to set email alerts
|

Novel heterozygous sequence variant in the GLI1 underlies postaxial polydactyly

Abstract: Polydactyly is one of the most common congenital abnormal phenotype of autopod, which is characterized by extra supernumerary digit in hands/feet with or without well‐developed bony structure within the digits. Preaxial polydactyly (PPD), postaxial polydactyly (PAP), and meso‐axial (central) polydactyly are three different isoforms of polydactyly. Genetically, at least 10 genes have been identified causing nonsyndromic polydactyly. In the present study, we have investigated a large family segregating autosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In our study, central polydactyly was observed only in 1 patient (patient 3). It is known that preaxial and postaxial polydactyly is a feature of CFNS, but central polydactyly, which is a rarely observed duplication of any of the central 3 digits (second, third and fourth) [Yousaf et al, 2020], has not been previously reported in this syndrome. Central polydactyly is a feature found in different syndromes including Orofaciodigital syndrome, Bardet Biedl syndrome, McKusick Kaufmann syndrome, and Synpolydactyly syndromes [Schaefer et al, 2013].…”
Section: Discussionmentioning
confidence: 91%
“…In our study, central polydactyly was observed only in 1 patient (patient 3). It is known that preaxial and postaxial polydactyly is a feature of CFNS, but central polydactyly, which is a rarely observed duplication of any of the central 3 digits (second, third and fourth) [Yousaf et al, 2020], has not been previously reported in this syndrome. Central polydactyly is a feature found in different syndromes including Orofaciodigital syndrome, Bardet Biedl syndrome, McKusick Kaufmann syndrome, and Synpolydactyly syndromes [Schaefer et al, 2013].…”
Section: Discussionmentioning
confidence: 91%
“…The same picture emerges when we examine missense variants in other GLI‐family members. Regarding GLI1 , variants segregating with dominant nonsyndromic A/B‐type PAP were recently reported, and all the missense variants (6 in all) were in the Zn‐fingers of GLI1 (Palencia‐Campos et al, 2020; Yousaf et al, 2020). Variable digital and other abnormalities in a large family segregated with a missense GLI3 variant Cys609Tyr in Zn‐finger number 5 (Crapster et al, 2017), and the same Zn‐finger was affected in a four‐generation family with Greig cephalopolysyndactyly syndrome segregating with a GLI3 p.(Arg625Trp) variant (Debeer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers also reported the incidence of PPD to be as high as 0.08 to 1.4 per 1,000 live births, while the prevalence of PAP is 1-2/1,000 live births with some ethnic group differences (Manske et al, 2017;Ullah et al, 2019a;Ullah et al, 2019b). In humans, until now, 11 genes (GLI3, GLI1, ZRS regulating LMBR1, IQCE, ZNF141, PITX1, MIPOL1, FAM92A, STKLD1, KIAA0825, and DACH1) and three other unknown loci have been mapped on different chromosome 13q21-32, 13q13.3-21.2, and 19p13.1-13.2, which have been linked with isolated polydactyly (Yousaf et al, 2020). However, eight of the 11 genes have been associated with isolated PAP type A including GLI family zinc finger three gene (GLI3; OMIM 174200; 7p14.1), zinc finger protein 141 gene (ZNF141; OMIM 615226; 4p16), GLI family zinc finger 1 (GLI1; OMIM 618123; 12q13.3), IQ Motif Containing E (IQCE; OMIM 617642; 7p22.3), KIAA0825 (OMIM 618498; 5q15), family with sequence similarity 92 member A1 (FAM92A; OMIM 618219; 8q22.1), and Dachshund Homolog 1 (DACH1; OMIM 603803) (Kalsoom et al, 2013;Umair et al, 2017Umair et al, , 2021 (Table 1).…”
Section: Introductionmentioning
confidence: 99%